2001
DOI: 10.1007/s002770100377
|View full text |Cite
|
Sign up to set email alerts
|

Ozonized autohemotransfusion improves hemorheological parameters and oxygen delivery to tissues in patients with peripheral occlusive arterial disease

Abstract: Twenty-seven subjects suffering from peripheral occlusive arterial disease (POAD, clinical stage II-III according to Fontaine) were enrolled in this study to evaluate the effect of oxygen-ozone therapy upon hemorheological parameters and hemoglobin-oxygen affinity in patients with POAD. All patients underwent a major ozonized autohemotransfusion consisting of the slow reinfusion of 100 ml of autologous blood, previously exposed to a O(2)-O(3) mixture in a glass box for 10 min. Whole blood viscosity, erythrocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
88
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(92 citation statements)
references
References 9 publications
1
88
0
3
Order By: Relevance
“…On the basis of preliminary in vitro and in vivo evidence, these simple laboratory parameters could be a useful complement in routine monitoring of biological compliance to treatment (34). Considered an alternative therapy, O 3 AHT has been increasingly used in the last few years and has been found useful in various diseases: -it activates the immune system in infectious diseases (21,25,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48); -it improves oxygen utilization and stimulates release of growth factors that reduce ischemia in vascular disease (10-12, 49, 50); -it activates the immune system and may improve the quality of life in cancer patients (25,49,51,52). Despite increasing use of O 3 AHT, the technique has not yet been fully accepted in scientific circles because its results have been modest, presumably due to the fact that only small quantities of blood could be treated (250 mL per treatment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of preliminary in vitro and in vivo evidence, these simple laboratory parameters could be a useful complement in routine monitoring of biological compliance to treatment (34). Considered an alternative therapy, O 3 AHT has been increasingly used in the last few years and has been found useful in various diseases: -it activates the immune system in infectious diseases (21,25,(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48); -it improves oxygen utilization and stimulates release of growth factors that reduce ischemia in vascular disease (10-12, 49, 50); -it activates the immune system and may improve the quality of life in cancer patients (25,49,51,52). Despite increasing use of O 3 AHT, the technique has not yet been fully accepted in scientific circles because its results have been modest, presumably due to the fact that only small quantities of blood could be treated (250 mL per treatment).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous non controlled trial, we observed very beneficial clinical effects of EBOO on PAD, especially the skin lesions, even deep and extensive ones (26,29). We obtained this clinical indication from the many articles published on the effects of O 3 AHT (12,22,24,37,40,49).…”
mentioning
confidence: 99%
“…Reactive oxygen species cause platelet aggregation and release of platelet-derived growth factors, transforming growth factor β, and interleukin-8, which play a major role in rapid wound healing 16. Ozone AHT is also shown to improve the hemorrheologic properties and increase the oxygen delivery to the more ischemic tissues 317. The therapeutic oxidative stress caused by the AHT also leads to upregulation of the intracellular antioxidant enzymes and production of heme oxygenase-1 and heat-stable protein-70, which help in protecting the tissues from ischemia/reperfusion and inflammation and also play a role in wound healing 3111820.…”
Section: Discussionmentioning
confidence: 99%
“…As, ozone therapy has been used as an adjuvant therapy in many vascular disorders such as ischemia of lower limbs, severe Raynaud's syndrome, obliteratives atheromatosis (Frankum & Katelaris, 1993;Tylicki, 2001;Tafil-Klawe, 2002;Cooke, 1997), peripheral occlusive arterial disease (Giunta, 2001) placenta insufficiency (Andikyan, 2000) and other vascular diseases (Bulmer, Bolton, & Pockley, 1997).…”
Section: Discussionmentioning
confidence: 99%